Analisis Senyawa Berbahaya Dalam Parfum Dengan Kromatografi Gas-Spektrometri Massa Berdasarkan Material Safety Data Sheet (Msds) - Iswara, Filasavita Prasasti; Rubiyanto, Dwiarso; Julianto, Tatang Shabur (Chemistry Department, Universitas Islam Indonesia, 2014)
This study was conducted to determine the harmful compounds in perfumes by gas chromatography-mass spectrometry (GC-MS). Perfume samples (A, B, C) obtained from the supermarket and the refill perfume fragrance that is almost the same. Methodology is the determination of specific gravity and refractive index. Chemical analysis performed using gas chromatography-mass spectrometry (GC-MS). Based on the results obtained three samples of data that have perfume composition profiles of the same constituent that is solvent, fixative agents, and perfuming agents. Compounds that are solvent are methanol, ethanol. Compounds that are fixative agent is 1,2-Butanediol, 3 ethoxy-1-propanol, limonene, dipropylene glycol, 2-(2-hydroxypropoxy)-1-propanol, 3,3’-oxybis-2-butanol. The compound is a substance which is dihydrojasmonat methyl fragrance, alpha-hexyl cinnamaldehyde. Dihydrojasmonat methyl is a compound that becomes the deciding factor perfume that smells like jasmine.